PENGARUH LAMA DAN SUHU PENGERINGAN TERHADAP MUTU BUBUK CABAI MERAH (Capsicum annuum L.) DENGAN MENGGUNAKAN CABINET DRYER - Dendang, Nataniel; Lahming, Lahming; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research aimed to determine the effect of drying time and temperature on the quality of red chili powder using the cabinet dryer. The research uses a completely randomized design (CDR) factorial pattern consist of 2 factors and 3 replications. Technique of data analysis using analysis of variance (ANOVA). The results showed that the drying time and temperature provides a significant influence on yield, moisture content, color, and pungency level of red chili powder. Treatment of 32 hours drying time and a drying temperature of 60oC provides the best results for the quality of red chili powder produced by the characteristic yield 14, 35%, moisture content 8,12%, color 4,48 (like), and the highest degree of spiciness